A MOUSE MODEL OF MAMMARY HYPERPLASIA INDUCED BY ORAL HORMONE ADMINISTRATION - Sun, Li; Guo, Dong-Hui; Liu, Fei; Qian, Liu; Jiang, Ning; Sun, Yun-Feng; Cai, Li-Ping; Zheng, Hong-Xin (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Mammary hyperplasia is one of the most common benign breast disorders. Although traditional Chinese medicine has a vast experience in the treatment of mammary hyperplasia, it is not accepted widely due to its unclear mechanism. Methods and Materials: To address the mechanism, we developed a mouse model of mammary hyperplasia. We gave mice estradiol valerate tablets and progesterone capsules sequentially for one month by intragastric administration. Results: Mice treated by this method had a series of pathological changes which are similar to those detected in women with mammary hyperplasia, including ectopic level of estradiol and progesterone in serum, hyperplasia of mammary glands and increased expression of ERα and PR. Conclusion: This model will facilitate the mechanical study of traditional medicine on mammary hyperplasia.